Gambaran deteksi dini masalah mental emosional anak taman kanak-kanak - Rohani, Siti; Wahyuni, Rini (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
Mental and emotional disorders are one type of developmental disorder in children. These disorders are all diagnosed with mental disorders and begin in childhood, including Attention Deficit Hyperactivity Disorder (ADHD), Tourette syndrome, behavior disorders, mood disorders and anxiety, autism spectrum disorders, and substance use disorders. This study aims to determine the description of Early Detection of Children's Mental Emotional Problems in the TK Aisyiyah Pringsewu Regency in 2019. The method used in this research is the univariate analysis method. This study used a quantitative descriptive research design. The population in this study were all children in Aisyiyah Pringsewu Kindergarten, Pringsewu Regency, as many as 80 children. The sampling technique in this study using total sampling. Univariate data analysis. Univariate analysis found that 32 respondents (40 percent) were male and 48 female respondents (60 percent), and 14 respondents (17.5 percent) who experienced emotional mental problems. 66 respondents (82.5 percent) did not experience mental-emotional problems. The results of this study can be used as input and additional knowledge to parents and school parents about the importance of the role of parents, especially mothers, families and the environment in the process of children's mental development.